2012
DOI: 10.1080/1091367x.2012.665268
|View full text |Cite
|
Sign up to set email alerts
|

Determining Intensity Levels of Selected Wii Fit Activities in College Aged Individuals

Abstract: To determine intensity of Nintendo Wii Fit games using indirect calorimetry. Twenty-five college students completed Wii Fit activity sessions at two difficulty levels within aerobics, strength, and yoga categories. Resting metabolic rate and exercise 2 O V  were measured and metabolic equivalents (METs) were calculated. Measured METs and calculated METs ranged from 2.30 ± .42 and 2.44 ± .38 for Yoga to 5.73 ± 1.36 and 6.04 ± 1.09 for aerobics, respectively. All selected Wii Fit activity intensities were signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
3
0
3
Order By: Relevance
“…Limited research on effects of these games has shown that AVGs can increase energy expenditure as compared to sedentary video games. 11 Although a small number of AVGs have been identified as providing moderate-intensity activity in youth, 12 studies suggest that most AVGs could only elicit light-to-moderate-intensity PA. 13 , 14 , 15 Research evidence summarized in a meta-analysis indicated that AVGs elicited higher energy expenditure in children than adults; thus, playing AVGs particularly benefits children. 15 …”
Section: Introductionmentioning
confidence: 99%
“…Limited research on effects of these games has shown that AVGs can increase energy expenditure as compared to sedentary video games. 11 Although a small number of AVGs have been identified as providing moderate-intensity activity in youth, 12 studies suggest that most AVGs could only elicit light-to-moderate-intensity PA. 13 , 14 , 15 Research evidence summarized in a meta-analysis indicated that AVGs elicited higher energy expenditure in children than adults; thus, playing AVGs particularly benefits children. 15 …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, kinetic technologies can, indeed, effectively enhance the attentive focus, interest and immerging power of learners on the courses studied with learning achievements well improved. Past researches sufficiently exert the interactively powerful functions of human-computer interfaces driven by kinetic technologies (Grieser et al, 2012;Hwang, Wu & Ke, 2013;Huang et al, 2012;Galatas, Ferdous & Makedon, 2013;Lee et al, 2011;Mentiplay et al, 2013;Qian, Niu & Yang, 2013;Vernadakis et al, 2012;Wachs et al, 2011). It is supportive for the materialization of kinetic teaching methods and instrumental in promoting bodily kinesthetic intelligence.…”
Section: Kinetic Technologiesmentioning
confidence: 99%
“…Οι επικείμενες διαφορές που αναφέρονται, πηγάζουν από το μικρό δείγμα του πληθυσμού, την ετερογένεια των δειγμάτων, τους διαφορετικούς τρόπους αξιολόγησης των εκάστοτε παραμέτρων, τους διαφορετικούς τύπους παιχνιδιών και τις μυϊκές ομάδες που χρησιμοποιούνται ανάλογα με το είδος και το επίπεδο δυσκολίας των ασκήσεων (Bailey & McInnis, 2011;Barnett et al, 2011;Biddiss & Irwin, 2010;Griese, Gao, Ransdell, & Simonson, 2012;Gunel et al, 2014;Peng et al, 2011;White et al, 2011).…”
Section: ενεργειακή δαπάνη και αδπunclassified
“…Συμπερασματικά, το σύνολο των ερευνών καταλήγει ότι τα ΑΔΠ μπορούν να αυξήσουν τα επίπεδα ΦΔ και να χρησιμοποιηθούν, προκειμένου να καλύψουν ένα μέρος της καθημερινής άσκησης (Griese et al, 2012;Lieberman, et al, 2011;Miyachi et al, 2010;White et al, 2008;Worley et al, 2011). Επιπλέον, αναφέρουν επιμέρους θετικές επιδράσεις στα στοιχεία της φυσικής κατάστασης για την υγεία, την κινητική απόδοση και τη συμπεριφορά (Carrasco et al, 2013;Green & Wilson, 2012;Hammond et al, 2014;Lawrence, 1986;Lotan, et al, 2010;Mejia-Downs et al, 2011;Weiss, Kizony, Fientuch, & Katz, 2006;Yalon-Chamovitz & Weiss, 2008).…”
Section: ενεργειακή δαπάνη και αδπunclassified
See 1 more Smart Citation